KEWENANGAN PEMERINTAH KABUPATEN/KOTA DALAM PENYELENGGARAAN URUSAN PEMERINTAHAN DI BIDANG PENDIDIKAN - Sabina, Vina; Maychellina, Maychellina; Fikri, Sultoni (Journal Evidence Of Law, 2023)
The purpose of this research is to describe the authority of district/city governments in managing government affairs in the education sector. As a consequence of the implementation of regional autonomy using the concurrent principle, there is a division of governmental affairs both at the central government and regional governments. This study focuses on the distribution of government affairs in the education sector. Because the study of government affairs in the education sector is small, the authors examine this matter. The research method is normative juridical research using statutory and conceptual approaches. The results of this study are because education is part of human rights, and the government is responsible for protecting, guaranteeing, and fulfilling the right to education for citizens. Then because of the consequences of implementing autonomy, then in terms of administering government affairs in the education sector, there is a division of functions. District/City Governments are tasked with overseeing the running of the education system in which local governments manage Early Childhood Education, Elementary Schools, and non-formal education as stipulated in laws and regulations.